Pola Asuh Orang Tua Dalam Membentuk Karakter Anak Usia Dini - Syamsiah, Syamsiah; Mulyadi, Mulyadi; Nurdiansyah, Erwin (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2023)
Research with the title description of parenting patterns in shaping the character of early childhood in tk aisyah mandalle. This research was conducted with the aim of knowing the effect of parenting in shaping the character of early childhood in Aisyiyah Kindergarten independently. The data collection techniques used in determining the truth of the problem are generally obtained through: Observation, Interview and Documentation. The results of the research conducted are, Early childhood is a group of children who are in the process of growth and development that is unique. Early childhood is often called preschool, which has a sensitive period in its development, and the maturation of physical and psychological functions that are ready to respond to stimuli from the environment. This period is the most appropriate time to lay the first and main foundation in developing various potentials and physical abilities, cognitive, language, art, social emotional, spiritual, self-concept, and independence. The parenting pattern given by parents is democratic parenting, which means that parenting tends to encourage children to be open, but responsible and independent. The results of the above research are in accordance with the results of interviews with neighbors that the author conducted as a crosscheck of the results of interviews with parents and also based on observations made by the author, that parents have indeed provided good parenting to children.